2006
DOI: 10.1108/00035590610650820
|View full text |Cite
|
Sign up to set email alerts
|

Some organic and inorganic compounds as inhibitors for carbon steel corrosion in 3.5 percent NaCl solution

Abstract: Purpose -To study the effects of the sodium salts of molybdate, tungstate and monovanadate as well as some derivatives of Neville-Winter acid azo dyes on the corrosion of carbon steel in 3.5 percent NaCl solution. Design/methodology/approach -Open circuit potential measurement and potentiostatic polarization techniques have been used. Findings -It was found that all the compounds had inhibition effects on carbon steel dissolution. Inhibition efficiency (IE) increased with increase in inhibitor concentration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The formation and development of this type of attack on the metal surface can occur only in solutions containing the aggressive Cl -, Br -and I -ions [4][5][6][7][8][9][10][11][12] . The critical potential at which pitting initiates is reported by several authors and found to depend on a number of factors including the type and concentration of attacking anion, type of metal used and relative concentration of other anions [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The formation and development of this type of attack on the metal surface can occur only in solutions containing the aggressive Cl -, Br -and I -ions [4][5][6][7][8][9][10][11][12] . The critical potential at which pitting initiates is reported by several authors and found to depend on a number of factors including the type and concentration of attacking anion, type of metal used and relative concentration of other anions [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of methods for protection against the corrosion of ferrous alloys, based on the use of corrosion inhibitors or coatings …”
Section: Introductionmentioning
confidence: 99%
“…2 (10) where E a represents the apparent activation energy, R the gas constant, T the temperature, A the pre-exponential factor, and W is the corrosion rate. The values of E a can be obtained from the slope of the straight lines and are listed in Table 4.…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…The use of inhibitors is one of the most practical methods for protection against corrosion especially in acid solutions to prevent metal dissolution and acid consumption [1]. Most well known acid inhibitors for steel corrosion are organic compounds containing [2][3][4][5][6][7][8][9][10]. It has been observed that most of the organic inhibitors act by adsorption on the metal surface [11].…”
Section: Introductionmentioning
confidence: 99%